2003
DOI: 10.1046/j.1095-8649.2003.00137.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of elevated summer temperatures on gonadal steroid production, vitellogenesis and egg quality in female Atlantic salmon

Abstract: Groups of Tasmanian female Atlantic salmon Salmo salar L. were maintained at 14, 18 and 22° C for 3 months from mid‐summer (January). Blood plasma levels of 17β‐oestradiol (E2), testosterone (T), cortisol and vitellogenin (Vtg) were measured at regular intervals, and in autumn (April) temperatures were reduced to 8° C to facilitate spawning and egg incubation. Maintenance at 22° C during vitellogenesis was associated with a general reduction in plasma E2 levels and an early reduction in plasma Vtg levels relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
91
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(103 citation statements)
references
References 30 publications
11
91
0
Order By: Relevance
“…HSI has been shown to be affected by the levels of various hormones, including E2 and insulin-like growth factor-1 (IGF-1). Since E2 treatment has been found to increase HSI and vitellogenin synthesis in numerous fish species (Osachoff et al 2013, Pandelides et al 2014, Park et al 2010) and elevated water temperatures impair E2 secretion (King et al 2003), we speculate that the elevated water temperature might have attenuated E2 secretion in our system, leading to the observed reductions in HSI. Long-term exposure to warm temperatures was previously shown to decrease IGF-1 levels, HSI values, and growth among juveniles of the southern flounder, Paralichthys lethostigma (Luckenbach et al 2007).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…HSI has been shown to be affected by the levels of various hormones, including E2 and insulin-like growth factor-1 (IGF-1). Since E2 treatment has been found to increase HSI and vitellogenin synthesis in numerous fish species (Osachoff et al 2013, Pandelides et al 2014, Park et al 2010) and elevated water temperatures impair E2 secretion (King et al 2003), we speculate that the elevated water temperature might have attenuated E2 secretion in our system, leading to the observed reductions in HSI. Long-term exposure to warm temperatures was previously shown to decrease IGF-1 levels, HSI values, and growth among juveniles of the southern flounder, Paralichthys lethostigma (Luckenbach et al 2007).…”
Section: Discussionmentioning
confidence: 90%
“…For example, exposure to high or low water temperatures was shown to attenuate gonadal maturation in both sexes of the pike-perch, Sander lucioperca (Hermelink et al 2011). High water temperatures reportedly damaged oocyte surfaces and reduced oocyte size via decreased levels of plasma gonadal hormone in the salmon, Salmo salar (King et al 2003). In the pejerrey, Odontesthes bonariensis, elevated temperatures reduced hormone levels in the brainpituitary-gonad axis, leading to gonadal regression and impaired spawning (Miranda et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the observed reduction in egg size suggests that exposure to elevated temperatures did have an effect on vitellogenesis in the present study. Reductions in final egg size in thermally stressed fish have been reported in rainbow trout (Pankhurst & Thomas 1998) and Atlantic salmon Salmo salar (King et al 2003). This was associated with reductions in plasma E 2 levels, and levels of the yolk precursor vitellogenin (in turn synthesized by the liver in response to stimulation by E 2 ) in Atlantic salmon, but no change in plasma E 2 in rainbow trout (Pankhurst et al 1996, Pankhurst & Thomas 1998.…”
Section: Discussionmentioning
confidence: 92%
“…Results showed that cortisol (as most physiological response to stress) reduces the Vtg protein levels without affecting the Vtg mRNA levels. King et al (2003) showed that temperature stress has adverse impact on follicular vitellogenesis of Atlantic salmon, Salmo salar L., 1758. In this regard, Maintenance at 22…”
Section: Introductionmentioning
confidence: 99%